Contact Interaction of Chromium Diboride with Iron-Based Self-Fluxing Alloy - Storozhenko, M. S.; Umanskyi, O. P.; Terentiev, O. Ye; Krasovskyy, V. P.; Martzenyuk, I. S.; Gubin, Yu.V. (Powder metallurgy and metal ceramics, 2022)
The contact interaction between a hot-pressed chromium diboride ceramic material and an ironbased self-fluxing eutectic alloy (FeNiCrBSiC) was studied. The structure and phase composition of the starting self-fluxing FeNiCrBSiC alloy were analyzed. The starting alloy consisted of chromium–molybdenum carbides and chromium–iron borides distributed in a nickel-based metal matrix. The wetting kinetics in the FeNiCrBSiC–CrB 2 system was studied by the sessile drop method in vacuum at 1150°C. The iron-based self-fluxing alloy was found to wet the chromium diboride substrate to form contact angle θ = 12º. The structural and phase composition of the droplet and the contact interaction area in the FeNiCrBSiC–CrB 2 system were examined by electron microprobe analysis. The FeNiCrBSiC–CrB 2 system was characterized by intensive chemical interaction, which led to the redistribution of components in the interaction and droplet areas. In the wetting process, boron from the upper layer of the CrB 2 ceramic substrate diffused to the alloy area. Further interaction of boron with chromium–molybdenum carbides present in the starting FeNiCrBSiC alloy resulted in chromium–molybdenum carboborides with up to 24 GPa microhardness. The droplet area had a heterophase structure, consisting of a nickel- and iron-based metal matrix and inclusions of superhard chromium borides. The FeNiCrBSiC–CrB 2 system can be considered promising for the development of composite materials because intensive chemical interaction between the alloy and refractory components leads to additional superhard chromium–molybdenum borides and carboborides in the matrix, promoting greater wear resistance of thermal spray coatings of the composite material.